Behaviors of soil cement columns and stiffened soil cement column wall in shallow excavation - I. Meepon; P. Voottipruex; P. Jamsawang (Lowland Technology International, 2016)
This research aims to presents results of laboratory investigations on cement-admixed clay and full scale of soil cement column (SCC) walls and stiffened soil cement column (SSCC) walls of 60 cm in diameter and 8 m depth constructed in soft Bangkok clay in various forms. There are five types of wall namely, type A: three row of soil cement column, type B: two rows of soil cement column, type C: one row of cement column inserted with steel H-beam in each column, type D: one row of soil cement column alternately inserted with H-beam, and type E: one row of soil cement column without reinforcement. The shallow excavation was conducted step by step with depth increment 1 m to 5 meter. Immediately after excavation; it can be observed from inclinometer that the horizontal movement of all type of wall exhibited slightly different. However, one day after excavation; the type A wall exhibited minimum movement of 6.37 mm; follow by type B wall with movement of 15.76 mm, and type C wall with movement of 22.37 mm. The maximum movement was observed from type D wall with movement of 51.99 mm while the type E wall failed one day after excavation. Alternate H-shaped steel reinforcement in the soil cement wall resisted bending moment due to lateral earth pressure up to a certain excavation depth. Beyond this depth the bending moment decreased, and the horizontal movement of the wall exhibited rigid body translation mode. The SSCC wall resisted bending moment due to lateral earth pressure through the embedded H-shaped steel in the soil cement column. Strain values indicated that the horizontal force was transferred to the embedded steel. Horizontal movement at the pile cap increased as the horizontal force increased. The SSCC continuously resisted the horizontal force through the embedded H-shaped steel, and a linear relationship between horizontal load and horizontal displacement was observed.